Scientific and technological prospection of Tabebuia reseoalba (Ipê-branco) (Research, Society and Development, 2021)
Tabebuia roseoalba, popularly known as Ipê-branco, a plant native to the Brazilian cerrado and wetlands. As it has numerous substances of therapeutic interest, there are perspectives of serving as an alternative in the control of infections. In order to verify the importance of the extracts of Tabebuia roseoalba in the scientific nature, researches were carried out in order to confirm the relevance that the present work presents as a technological innovation. The results found in the Science Direct and Pubmed databases, as well as the patents found in the World Intellectual Property Organization (WIPO) and National Institute of Industrial Property (INPI) patent databases, were effective methods for the construction of this Prospectus. From the keywords antimicrobial, bacterial resistance, Bignoniaceae, Tabebuia and Tabebuia roseoalba, in English and Portuguese, when necessary, the WIPO patent database revealed 135,638 patents for antimicrobial, 78,108 for bacterial resistance, 69 for Bignoniaceae, 167 for Tabebuia and 0 for Tabebuia roseoalba. The INPI obtained 1,377 for antimicrobial, 2,510 for bacterial resistance, 38 for Bignoniaceae, 31 for Tabebuia and 3 for Tabebuia roseoalba. From the results obtained through patent searches on the use of antimicrobial potentials from Tabebuia roseoalba to combat pathogens, it can be concluded that the study provided data from scientific-technological prospection, as it helped as a good tool for the carrying out this research, the importance of technological prospecting analysis can be highlighted, as a beneficial means in which it can promote the ability to organize innovative research based on the interests and needs of society.